ANTIOXIDANT ACTIVITY OF BLUMEA BALSAMIFERA L. LEAVES EXTRACTS - Binawati Ginting; Maulidna Maulidna; Nurdin Nurdin; Aida Lisma (PROSIDING SEMINAR KIMIA, 2021)
Blumea balsamifera L leaves were isolated and tested for antioxidant activity using the 1,1-diphenyl-2-picrylhydrazyl(DPPH) method. B. balsamifera leaves were macerated as much as 1300 gram using a methanol solvent thenpartitioned with petroleum ether, n-hexane, and extracted with ethyl acetate and acetone to obtain petroleum ether, nhexane, ethyl acetate, acetone and methanol extracts by weight and% yield respectively, namely 6.34 g (5.43%), 4.97 g(4.25%), 7.34 g (6.28%), 14.14 g (12.11%) dan 5.66 (4.85%). Phytochemical tests of petroleum ether and n-hexaneextracts showed the presence of steroid compounds, while ethyl acetate, acetone, and methanol extracts showed thepresence of alkaloids, saponins, flavonoids, terpenoids, and phenolic compounds. The antioxidant activity test ofpetroleum ether, n-hexane, ethyl acetate, acetone, and methanol extracts obtained IC50 values respectively 177.47 ppm,192.66 ppm, 4.28 ppm, 7.33 ppm and 8.61 ppm. Acetone extract of B. balsamifera (BBA) is separated by chemicalcomponents using chromatography of gravity column so that the combined fraction of acetone B. balsamifera extract(BBA1-BBA11) is obtained. Antioxidant activity test of BBA1, BBA2, BBA3, BBA4, BBA5, BBA6, BBA7, BBA8, BBA9,BBA10 and BBA 11 fractions IC50 values obtained were 147.17 ppm, 81.36 ppm, 10.31 ppm, 3.84 ppm, 1.18 ppm, 3.37ppm, 6.76 ppm, 9.32 ppm, 19.26 ppm, 16.82 ppm, and 30.71 ppm. The BBA extract is characterized by its structureusing Gas Chromatography-Mass Spectrometry (GC-MS).Keywords: Blumea balsamifera L leaves, acetone extract, Antioxidant activity, 1-diphenyl-2-Pikrilhidrazil (DPPH)